2019
DOI: 10.36380/scil.2019.ojafr28
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of parasitic honeybee diseases, pests and predators in North Gondar zone.

Abstract: A cross-sectional study was conducted on parasitic honeybee diseases, pests and predators Lay armachiho and Tach armachiho districts of North Gondar zone from October 2017 to May 2018. The objectives of this study were to assess the different parasitic honeybee diseases, pests and predators. The study mainly involves with the collection of adult honeybee abdominal suspension of wet mount for nosema and amoeba diseases and direct observation of varroa mite and bee louse from adult honey bee and brood cells. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
3
3
0
Order By: Relevance
“…This might be due to the effect of temperature and humidity that affect the spread of N. apis . The current finding is in agreement with the finding of Nega et al [ 43 ] who stated that an increase in humidity and rainfall limit honeybees to fly out for cleansing, which in turn enhances the spread of the disease among the members and autoinfection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This might be due to the effect of temperature and humidity that affect the spread of N. apis . The current finding is in agreement with the finding of Nega et al [ 43 ] who stated that an increase in humidity and rainfall limit honeybees to fly out for cleansing, which in turn enhances the spread of the disease among the members and autoinfection.…”
Section: Discussionsupporting
confidence: 93%
“…e current finding is in agreement with the finding of Nega et al [43] who stated that an increase in humidity and rainfall limit honeybees to fly out for cleansing, which in turn enhances the spread of the disease among the members and autoinfection. e overall prevalence of N. apis has a significant variation between hives (p < 0.02), and it was higher in traditional than both modern and transitional hive types.…”
Section: Discussionsupporting
confidence: 93%
“…Results indicated that the prevalence of bee lice was higher in modern beehives (31.3%) than tradition beehives (22.2%), as well as in midland than highland (Table 8), but the p-value of a chi square showed no significant association for both factors. The higher prevalence of the bee at lower altitudes is in agreement with the report in the Northern Gondar of the Amhara Region [11]. The overall prevalence of small hive beetles was 11.7% in the study area (Table 9).…”
Section: Prevalence Of Honeybee Pestssupporting
confidence: 90%
“…However, the association between amoeba prevalence and agro-ecology as well as hive type was not significant (p > 0.05). Although similar results have been reported that amoeba is more common in highland areas than lowland and midland agro-ecologies [13] as well as in traditional hives than modern hives [11], these works did not state whether there was an association between agro-ecologies as well as hive types or not. Moreover, amoeba was more prev-alent in traditional hives than modern hives, which is similar with the previous in North Gondar.…”
Section: Prevalence Of Honeybee Diseases and Pestsmentioning
confidence: 56%
“…Several studies conducted in Ethiopia have examined the prevalence of Varroa infestation in honeybee colonies and reported a high prevalence ranging from 30.5% to 91.8%. Furthermore, the infestation has been reported to have significant detrimental effects on both honeybee colonies and honey production, posing a considerable challenge for the country's beekeeping industry ( Begna, 2015 ; Godifey, 2015 ; Mezgabu et al, 2016 ; Nega et al, 2019 ; Shegaw et al, 2022 ; Gela et al, 2023 ). Furthermore, studies have shown that Ethiopian honey bee antennae exhibit an increased level of gene expression of the odorant binding protein OBP14, suggesting a potential improvement in detection and elimination of reproducing mites ( Gebremedhn et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%